Probing dipole-forbidden autoionizing states by isolated attosecond pulses - Chu, Wei-Chun; Morishita, Toru; Lin, C. D. (My University, 2014)
We propose a general technique to retrieve the information of dipole-forbidden resonances in the autoionizing region. In the simulation, a helium atom is pumped by an isolated attosecond pulse in the extreme ultraviolet (EUV) combined with a few-femtosecond laser pulse. The excited wave packet consists of the 1S, 1P, and 1D states, including the background continua, near the 2s2p(1P) doubly excited state. The resultant electron spectra with various laser intensities and time delays between the EUV and laser pulses are obtained by a multilevel model and an ab initio time-dependent Schrödinger equation calculation. By taking the ab initio calculation as a “virtual measurement,” the dipole-forbidden resonances are characterized by the multilevel model. We found that in contrast to the common assumption, the nonresonant coupling between the continua plays a significant role in the time-delayed electron spectra, which shows the correlation effect between photoelectrons before they leave the core. This technique takes the advantages of ultrashort pulses uniquely and would be a timely test for the current attosecond technology.